(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
“Peste des Petits Ruminants (PPR is a contagious viral disease of small ruminants in Africa and Asia). In this study, the epidemiology of PPR in sheep in River Nile and White Nile States was investigated. For this purpose, the sero-prevalence of PPR in these two states was determined by using cELISA and the risk factors associated with the sero-prevalence were investigated. In a total of 519 serum samples that fall within the recommended 95% level of confidence (Thrusfield, 2007), a 53% prevalence (275/519) was found; 56.5% (147/260) in River Nile state and 49.4% (128/259) in White Nile state. This statistically insignificant difference (P=0.104) in PPR prevalence in the two states could be attributed to similar animal movements and communal grazing and watering among animals of the two states. In the unvariate analysis, 15 statistically significant factors that had an impact on PPR spread were determined. These were: Locality (pvalue=0.000), sex (p- value=0.000), age (p- value=0.000), herd composition (p- value=0.002), migratory routes (p- value=0.000), cleaning (pvalue=0.000), known signs of PPR (p- value=0.011), season (pvalue=0.000), morbidity rate (p- value=0.001), mortality rates (pvalue=0.000), abortion (p- value=0.000), affecting production (pvalue=0.002), loss during year (p- value=0.000), using outside rams (pvalue=0.011) and vaccination of PPR (p- value=0.000) while in multivariate analysis only one risk factor was found statistically significant which is sex (p- value=0.000). Risk factors significantly associated with a cELISA positive status for PPR in this study could be considered as important predictors for the occurrence of PPR outbreaks in these states